Immunohistochemical Analysis of Vimentin and Zonula Occludens-1 in Placentas of Patients with PPROM - Fuat Zaman; Fırat Aşır; Işılay Sezen Ermiş; Mehmet Cudi Tuncer; Engin Deveci; Süleyman Cemil Oğlak (IMR Press, 2024)
Background: We aimed to investigate the immunohistochemical staining of vimentin and zonula occludens-1 (ZO-1) expression in the placentas of pregnant women with preterm premature rupture of membranes (PPROM). Methods: Placentas of 25 healthy and 25 women with PPROM were fixed in 10% formaldehyde solution and further processed for paraffin wax tissue embedding. Demographic properties of patients were recorded. Placentas were histologically stained with hematoxylin-eosin and vimentin and ZO-1 expression immunostaining. Results: Vimentin expression was high in the decidual cells, fibroblasts, and connective tissue fibers in control group. Compared to control group, vimentin expression was decreased in the placental structures of PPROM group, where fetal membranes were degenerated and histologically irregular. Similar to vimentin expression, ZO-1 expression was also high in placental components of control group such as chorioamniotic membrane and amniotic epithelium. The PPROM group showed lower expression of ZO-1 expression in placental structures than in that of control. ZO-1 expression was significantly lowered in regions where fetal membrane integrity was weakened and lost. Conclusions: We suggest that ZO-1 and vimentin expression may show alteration in etiology premature rupture of membrane.